Attitude of Youths to Agriculture as Career in Iwo and Aiyedire Local Government Areas of Osun State, Nigeria - F. E, Nlerum; F. J, Babatunde (International Journal of Sustainable Agricultural Research, 2019)
The study determined the attitude of youths to agriculture as a career in Iwo and Aiyedire Local Government Areas of Osun State, Nigeria. The sample size of the study was 90 youths who were randomly selected from the clans of the study area. The questionnaire was the instrument used for data collection. Data were analyzed with mean and t-test. Results showed that the attitude of youths to agriculture as a career in the study area was negative as indicated by grand means of 2.44 and 2.47 in Iwo and Aiyedire respectively. The variable with the highest negative response in Iwo with a mean of 2.32 was that agriculture is a gold mine for young entrepreneurs. For Aiyedire the variable with the highest negative response of 2.42 was that agriculture is attractive and decent. The major constraints of the youths to the choice of agriculture as a career in Iwo were insufficient land to start (3.02) and use of crude tools for farming (3.02). Lack of funds to begin (2.91) and insufficient career guidance by agricultural extension workers and rural sociologists (2.79) were the major constraints for youths in Aiyedire. In order to attract more youths into having a positive attitude to agriculture as a career, the study recommends provision for sufficient land and fund for young farmers and engagement of more agricultural extension workers and rural sociologists for career guidance to youths in the study area.